Phytochemical Analysis and α-Amylase Inhibitory Activity of Young and Mature Leaves of Cinnamomum tamala - Maharjan, Rasna; Thapa, Prakash; Khadayat, Karan; Kalauni, Surya Kant (Nepal Journal of Biotechnology, 2021)
The bioactive chemical components of the plant’s origin have been used as primary remedies for a wide array of human diseases including diabetes. The present research deal to evaluate and compare anti-diabetic potential of ethanolic and methanolic, young and mature leaves of medicinally valuable Cinnamomum tamala. Total phenolic and flavonoid contents of young and mature leaves were determined. In vitro α-amylase inhibition was carried out using 2-chloro-4-nitrophenyl-α-D-maltotrioside (CNPG3) as substrate. Phytochemical screening revealed the presence of polyphenols, flavonoids, terpenoids, quinones, carbohydrates, glycosides, diterpenes, tannins, and reducing sugars. The highest total phenolic content and flavonoid content were observed in methanolic extract of mature leaves (13.725 ± 0.54 mg GAE/g) and young leaves (12.591 ± 0.71 mg QE/g) respectively. Methanolic young leaves extract showed α-amylase inhibition with IC50 value 224.6 ± 2.76 μg/mL as compared to acarbose with IC50 value 5.93 ± 0.14 μg/mL. The result suggests that young leaves of C. tamala had anti-diabetic activity so further work should be carried out.